Applications of VUV extra‐focus mechanism: high‐performance dual‐mode monochromator from VUV to soft X‐ray. (29th September 2015) - Xue, Chaofan; Wu, Yanqing; Zou, Ying; Xue, Lian; Guo, Zhi; Wang, Yong; Tai, Renzhong
Abstract : A new monochromator scheme is presented in which an extra‐focus constant‐included‐angle varied‐line‐spacing cylindrical‐grating monochromator (extra‐focus CIA‐VCGM) is conveniently combined with a variable‐included‐angle varied‐line‐spacing plane‐grating monochromator (VIA‐VPGM). This dual‐mode solution delivers high performance in the energy range from vacuum ultraviolet (VUV) to soft X‐ray. The resolving power and the efficiency of this dual‐mode grating monochromator are analyzed in detail based on realistic parameters. Comparisons with the commonly used variable‐included‐angle plane‐grating monochromator and normal‐incidence monochromator (VIA‐PGM/NIM) hybrid monochromator are made.